EVALUATION OF PROBLEMS AND POSSIBILITIES OF INDUSTRIAL FISH UTILISATION FOR HUMAN CONSUPTION - Motova, Arina; Zolubas, Tomas (Ekonomika, 2010)
Fish caught by Lithuanian Baltic Sea fishermen is used for industrial purposes to a relatively large proportion – 60–80 percent of the total volume versus 25–30 percent on the global level. There is no fully developed fishmeal industry in Lithuania, so industrial fish species are disposed of at foreign markets. The first sale prices for fish used for human consumption are higher. It is considered that saling sprats and herrings for human consumption would increase fishermen’s income, create an additional profit and value added. The purpose of the study was to determine the economic reasons why a large portion of Lithuanian landings of Baltic Sea pelagic fish species are used for industrial purposes. The study has shown that the main reasons are unstable, seasonal supply of sorted and good quality raw material and the lack of production sales markets. The authors have investigated the problem and proposed possibilities to increase the use of industrial fish for human consumption in Lithuania.